Anti-inflammatory effects of Andrographis paniculata (Fah Talai Jone) via TNFα-JNK pathway and bioactive compound identification - Praphat Manuelo Ruengthanoo; Areeya Changthong; Pranee Sriraj; Jatuporn Prathumtet; Nutchapon Laikaew; Ratchadawan Aukkanimart (Phytomedicine Plus)
Background: Andrographis paniculata (Fah Talai Jone), a widely used medicinal plant in traditional medicine, is known for its anti-inflammatory properties. This study investigates its bioactive compounds and their role in alleviating inflammation through the TNF-α-JNK pathway. Purpose: The aim of this study was to identify bioactive compounds in A. paniculata extracts and evaluate their anti-inflammatory effects, focusing on the TNF-α-JNK pathway. Study Design: Experimental research was conducted to assess the antioxidant, cytotoxic and anti-inflammatory properties of both ethanol (APE) and aqueous (APA) extracts of A. paniculata using in vitro methods. Methods: Ethanol (APE) and aqueous (APA) extracts of A. paniculata were prepared and analyzed for total phenolic and flavonoid content, antioxidant activity, and bioactive compound identification using high-performance liquid chromatography (HPLC). Cytotoxicity was evaluated using the sulforhodamine B assay, and the anti-inflammatory effects were assessed through cellular assays measuring reactive oxygen species (ROS) production and JNK pathway modulation. Results: HPLC analysis identified andrographolide as the primary bioactive compound in APE (186.6 ± 2.53 µg/mg). APE exhibited higher phenolic (8.66 ± 0.37 mg GAE/g) and flavonoid (156.33 ± 4.76 mg QE/g) content compared to APA. Antioxidant assays revealed IC50 values of 11.14 ± 1.07 µg/ml for APA and 2.29 ± 0.13 µg/ml for APE. Cytotoxicity studies demonstrated that both extracts were non-toxic to lung cells. APE significantly reduced ROS production (68.3 ± 7.64 % at 62.5 µg/ml) and decreased JNK phosphorylation, indicating its anti-inflammatory potential. Conclusion: Andrographis paniculata, particularly its ethanol extract, exhibits potent antioxidant and anti-inflammatory effects mediated by andrographolide. These findings support its potential as a natural therapeutic agent for managing inflammation.